Prevalence of congenital missing permanent teeth and its association with side and gender in a Saudi subpopulation - Abdulrahman K. Alshammari; Muteb A. Algharbi; Freah L. Alshammary; Nabeel S. Almotairy; Hatem D. Alshammari; Ibrahim R. Altheban; Khalid A. Aljameel; Fahad M. Aldakheel; Ahmed A. Madfa (PLoS ONE, 2025)
Background This study’s objectives are to ascertain the frequency of congenital tooth missing and evaluate the relationship between gender and side characteristics. Method This retrospective study involved participants who attended private dental clinics as well as a dental college in Hail, Saudi Arabia. Out of the 1,150 patients examined, 494 (220 males and 274 females) fulfilled the inclusion criteria. Different types of tooth agenesis were evaluated and classified into the following categories: mild (one or two teeth missing), moderate (three to five teeth missing), and severe (six or more teeth missing). The analysis did not include third molars. The existence of retained primary teeth was noted, along with any dental abnormalities accompanying tooth agenesis. Statistical analysis was conducted utilizing the chi-square test and Fisher’s exact test to explore possible relationships between variables. A significance level of 5% (alpha = 0.05) was utilized. Results Out of the 1150 panoramic radiographs that were examined, 494 individuals (220 (44.5%) males and 274 (55.5%) females) met the criteria for inclusion. The prevalence of congenitally missing permanent teeth was 65 (13.2%) in the study sample. The prevalence of congenitally missing teeth were more incidence in maxilla 36 (56.3%) than mandible 28 (43.8%). There is statistically significant association between the occurrence of congenitally missing teeth and gender or arch (p < 0.05). The prevalence of dental anomalies was similar in both sides. There are not a statistically significant association (p > 0.05) between the occurrence of congenitally missing teeth and side. The second premolar was the most commonly missing (7.3%). The retained deciduous teeth was shown to be the most common dental anomaly, with a prevalence of 15 (23.4%). Conclusions The prevalence of congenitally missing teeth fell within the range reported in previous studies. Second premolars were the most frequently congenitally missing teeth, with maxillary teeth more commonly affected than mandibular ones.